Program CSR ceria dan cergas: senyuman bersama Rumah Kanak Kanak Rembau / Muhammad Faris Amirul Useri and Raja Al-Imran Hakim Raja Nor Azlan - Useri, Muhammad Faris Amirul; Raja Nor Azlan, Raja Al-Imran Hakim (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The ‘Ceria Dan Cergas: Senyuman Bersama’ program was an event organized as part of our coursework assessment. This event's main objective is to strengthen relationships between The Faculty of Sport and Recreation students and the Community, specifically by providing services to children from Rumah Kanak Kanak Rembau, Negeri Sembilan. Background of Rumah Kanak Kanak Rembau Rumah Kanak-Kanak Rembau is a safe place institution for the care and protection of children designated under section 54 (safe place) of the Children's Act 2001. This institution provides substitute care for children in addition to promoting healthy physical, emotional, and mental growth. The children are also given support to grow and develop in a harmonious family atmosphere.